KATA KERJA DALAM BAHASA MELAYU DIALEK SANGGAU DI MELIAU - Ariyani, Fitria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research deals with the field of morphology, especially about of verbs BMDS in Meliau. The research was distributed by the ins and outs of the structure of words and the influence of changes in the structure of the word against word class and word meanings in the Malay language. The problem that is discussed in this research is the description of the verb form, the process of formation of the noun verb, verb syntax function in BMDS in Meliau. This research uses descriptive Linguistics methods with qualitative form. Data collection techniques used refer to the look, interviews, Record and note the data Gatherer with a tool in the form of a list of the basic verb form in English then translated into the Malay language. Based on the data analysis there are as many as 120 verb, each taken data derivation of nouns into verbs, adjectival derivation into a verb, adverb derivation into a verb, and the verb itself. The study was successfully brought together 115 Malay dialect verbs, while the 5 verbs cannot decline verbs. The function of this verbs is a verb functioning as a predicate, object, subject, job description, and complement. Keyword : verb, BMDS in Meliau